Interdisciplinary considerations for diagnosing aphasia in the schizoaffective patient: A case report - Warner, Heather; Cometz, Alexa (International Journal of Language & Communication Disorders, 2023)
Background Patients with schizophrenia present with both cognitive impairment as well as language difficulties. There are similarities in the language output of patients with schizophrenia and patients with aphasia, thus a differential diagnosis of patients who present with a question of dual diagnoses can be a clinical challenge. This case report highlights the importance of an interdisciplinary approach to a patient with schizophrenia who benefitted from intervention from both psychiatry and speech–language pathology services due to the patient's unique verbal output. Aims The primary aim of this case report is to highlight the critical importance of interdisciplinary collaboration in this patient population. The secondary aim is to disseminate an interesting and unique clinical phenomenon whereby the patient demonstrated an awareness of two distinct speech patterns and the unique ability to ‘code switch’ between them, something not commonly appreciated in this clinical population. Methods & Procedures This case report describes a patient seen as part of routine clinical care. Information shared was solely observational and involved dissemination of information regarding case history, assessment and treatment plan. No interventions were implemented as a part of this study. Outcomes & Results Interprofessional communication was critical in order to diagnose a patient with schizophrenia with an atypical speech pattern. The patient's language output did not manifest as a true aphasia but rather as two distinct language patterns that the patient could use at will. This ability to ‘code switch’ between languages is a unique clinical profile that is atypical of patients with schizophrenia. WHAT THIS PAPER ADDS What is already known on this subject Contemporary literature discusses the similarities between the language patterns of patients with aphasia and those with schizophrenia. There has been debate about how to classify and identify the mechanism of schizophrenic language. It is unclear whether the tangential press of speech in schizophrenia is a consequence of a formal thought disorder, or whether it constitutes an actual disorder or expressive language. Additionally, the mechanism for this speech pattern is not well defined in the literature as there is no consensus on whether it is a breakdown in linguistic processing or simply a patient's disordered thoughts being put into words. A less robust literature exists that suggests that there is a cognitive mechanism responsible for these speech patterns, as tangential speech has been linked to poor goal maintenance in other types of cognitive tasks. What this paper adds to existing knowledge This study adds an important discussion about the critical importance of interprofessional collaboration when differentially diagnosing this complex patient population. It highlights the importance of the clinical exchange of information between the two disciplines of psychiatry and speech–language pathology about a patient population where clinical information is intertwined in the way described above. Regardless of the cause of the disordered output, what is lacking in the literature is evidence of how to address the complexities of the output of these patients and how to best manage the care of the patient. This study adds a practical clinical approach to collaborating on the assessment and management of this complex patient population. Importantly, it adds a description of a clinical manifestation of the language output of a patient with schizophrenia that we do not believe to have been previously published in the literature. What are the potential or actual clinical implications of this work? Implications of this study include a much-needed shift in the field in two regards. First, to include this patient population in the groups of patients that can benefit from interprofessional collaboration for differential diagnosis and consideration for speech and language therapy. Second, it offers a practical clinical approach to inter-professional management in this patient population, something the literature is currently lacking. Additionally, publication of this unique clinical manifestation provides foundational knowledge for other clinicians appreciating similar clinical patterns of language output. To our knowledge, this is the first published case in which a patient could volitionally inhibit certain speech characteristics and thus this case study may assist in future differential diagnosis of patients with schizophrenia.
1 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1460-6984.12801
Keywords: aphasia; dept.cmd; interprofessional practice; language disorders; peer-reviewed; schizoaffective disorder

Utilization of instrumentation in swallowing assessment of surgical patients during COVID-19 - Warner, Heather; Coutinho, Jennifer M.; Young, Nwanmegha (Life, 2023)
The aim of this study is to describe a measured return to instrumental dysphagia assessments for our vulnerable surgical patient population, such that best practice patterns could be resumed and our staff kept safe from transmission of COVID-19. A retrospective medical record review provided data on clinical practice patterns of swallowing assessment in an at-risk surgical patient population. Outcomes of this study support protocols that allow clinicians to safely resume the use of instrumental assessment and return to best practice in dysphagia assessment for our surgical patient population.
0 citations (Crossref) [2023-10-31] Number: 7
Keywords: COVID-19; Fiberoptic Endoscopic evaluation of swallowing; deglutition; dept.cmd; dysphagia; peer-reviewed; surgical; swallowing assessment